Issues relating to the practical use of transgenic crops for insect pest management - Teulon, D.A.J.; Losey, J.E. (New Zealand Plant Protection, 2002)
The implementation of transgenic plants for insect pest management requires a thorough evaluation of the risks costs and benefits Currently all commercialised transgenic crops for insect control contain genes expressing specific Bt toxins Excluding environmental and human health concerns the most apparent risk for these Btplants is development of resistance to Bt toxins The high dose/refuge strategy is accepted as most likely to delay or prevent pest resistance development This strategy is based on the best available information but has several incompletely tested assumptions The high dose/refuge strategy requires detailed knowledge of the plantinsect system and its implementation involves rigorous crop management There have been few documented instances of harmful impacts on predators and parasitoids from transgenic plants expressing Bt or other toxins The costs and benefits of using transgenic plants will depend on several factors including the plant species its complex of insect pests environmental conditions and alternative pest management tools and systems such as Integrated Pest Management Benefits of transgenic plants are most likely to outweigh costs and risks for insects that are difficult to control by any other method and/or require numerous insecticide applications